Alternative Splicing Modulates Ubx Protein Function in Drosophila melanogaster - Reed, Hilary C. (Genetics Society of America, 2010)
The Drosophila Hox gene Ultrabithorax (Ubx) produces a family of protein isoforms through alternative splicing. Isoforms differ from one another by the presence of optional segments—encoded by individual exons—that modify the distance between the homeodomain and a cofactor-interaction module termed the “YPWM” motif. To investigate the functional implications of Ubx alternative splicing, here we analyze the in vivo effects of the individual Ubx isoforms on the activation of a natural Ubx molecular target, the decapentaplegic (dpp) gene, within the embryonic mesoderm. These experiments show that the Ubx isoforms differ in their abilities to activate dpp in mesodermal tissues during embryogenesis. Furthermore, using a Ubx mutant that reduces the full Ubx protein repertoire to just one single isoform, we obtain specific anomalies affecting the patterning of anterior abdominal muscles, demonstrating that Ubx isoforms are not functionally interchangeable during embryonic mesoderm development. Finally, a series of experiments in vitro reveals that Ubx isoforms also vary in their capacity to bind DNA in presence of the cofactor Extradenticle (Exd). Altogether, our results indicate that the structural changes produced by alternative splicing have functional implications for Ubx protein function in vivo and in vitro. Since other Hox genes also produce splicing isoforms affecting similar protein domains, we suggest that alternative splicing may represent an underestimated regulatory system modulating Hox gene specificity during fly development.